2018
DOI: 10.1021/acs.iecr.7b04147
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific Ionic Liquids as Extractants for the Solvent Extraction of Molybdenum(VI) from Aqueous Solution Using Different Commercial Ionic Liquids as Diluents

Abstract: In this work, the recovery of molybdenum­(VI) (Mo) from aqueous solutions was carried out by solvent extraction (SX) using ammonium and phosphonium-based task-specific ionic liquids (TSILs) as extractants diluted in kerosene and two other hydrophobic room-temperature ionic liquids (RTILs). Four different TSILs were used as extractants: trioctylmethylammonium bis­(2-ethylhexyl) phosphate [TOMA]­[D2EHP]; trioctylmethylammonium benzoate [TOMA]­[BA]; trihexyltetradecylphosphonium bis­(2-ethylhexyl) phosphate [P6,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Furthermore, a problem associated with the use of ILs as extractants is their high viscosity; therefore, they are dissolved in molecular solvents. This approach allows for producing highly efficient extraction systems for the recovery of indium(III) and gold(III) from electronic waste [21,22] and Mo(VI) in high (more than 99%) yields [23].…”
Section: Ionic Liquids As Extractants In Extraction Systemsmentioning
confidence: 99%
“…Furthermore, a problem associated with the use of ILs as extractants is their high viscosity; therefore, they are dissolved in molecular solvents. This approach allows for producing highly efficient extraction systems for the recovery of indium(III) and gold(III) from electronic waste [21,22] and Mo(VI) in high (more than 99%) yields [23].…”
Section: Ionic Liquids As Extractants In Extraction Systemsmentioning
confidence: 99%
“…Recent works have proposed ILs as extractants, where the most important achievement is that high extraction percentages were reported with only a small concentration of them in a diluent, 14,15 when compared to conventional extractants. In this sense, in previous works, the IL trioctylmethylammonium benzoate [TOMA][BA] has been introduced as an extractant, for Mo(VI) extraction, showing high extraction percentages (90–100%) at low pH values and with a small amount of this extractant (1% v/v) 14 . A recent work showed that the IL tricaprylmethylammonium nitrate ([A336][NO 3 ]) extracted negatively charged vanadium, V(V), species (V4O124 or V3O93) from acid solutions 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, in previous works, the IL trioctylmethylammonium benzoate [TOMA][BA] has been introduced as an extractant, for Mo(VI) extraction, showing high extraction percentages (90-100%) at low pH values and with a small amount of this extractant (1% v/v). 14 A recent work showed that the IL tricaprylmethylammonium nitrate ([A336][NO 3 ]) extracted negatively charged vanadium, V(V), species (V 4 O −4 12 or V 3 O −3 9 ) from acid solutions. 16 This latter IL contains a similar cation to the proposed in this work, which allows extraction of the V(V) species, demonstrating that [TOMA] − could extract anionic species of Re(VII) present in a wide range of pH values in a sulfuric acid medium.…”
Section: Introductionmentioning
confidence: 99%
“…The above research can realize the selective separation of Co 2+ and the recovery of Co 2+ products by stripping, 18 but there are two problems in the extraction process: (1) the extraction system composed of kerosene and organic extractant is easy to volatilize due to its relatively high saturated vapor pressure, 40 which is easy to cause damage to the operator's body and environment. 41 (2) The extraction system easily accumulates static electricity due to low conductivity, and a large number of volatile solvents is used in the separation process.…”
Section: ■ Introductionmentioning
confidence: 99%